Pengabdian Kepada Masyarakat Melalui 7 Langkah Mencuci Tangan Dengan Baik Dan Benar Kelurahan Galang Baru Kota Batam - Sri Hainil; Suhaera Suhaera; Suci Fitriani Sammulia; Hesti Marliza; Nanda Siska; Sri Rahayu Melpa Sari (Pusat Riset dan Inovasi Nasional, 2021)
Washing your hands is one way to remove germs and to avoid disease transmission. The habit of Indonesian children in washing their hands is still in the low category. At school, children not only learn, but there are many other activities that children can do at school, such as playing, touching or exchanging things with friends. Hand washing must be taught to children from an early age so that children have the habit of washing their hands, so that children avoid disease. Standard recommendations for preventing the spread of infection are through washing hands regularly using soap and clean water, implementing coughing and sneezing etiquette, avoiding direct contact with livestock or wild animals and avoiding close contact with anyone showing symptoms of respiratory disease such as coughing and sneezing. Clean and Healthy Living Behavior (PHBS) is a set of behaviors that are practiced on a conscious basis as a result of learning that enables a person or family to help themselves in the field of health and play an active role in realizing public health. Healthy conditions can be achieved by changing unhealthy behavior to healthy behavior and creating a healthy environment in the household. Therefore, health needs to be maintained, maintained and improved by every member of the household and fought for by all parties. The introduction of Clean and Healthy Living Behavior (PHBS) in elementary school education is able to maintain, improve and protect the health of each household member from the threat of disease and an environment that is less conducive to healthy living. Washing your hands with soap can kill the virus that causes infection from your hands before the virus infects the body. Apart from that, washing your hands regularly can also reduce the spread of the virus to other people.